The Influence of Competence, Professional Ethics, and Information Technology on Audit Quality : Empirical Study at South Jakarta Public Accounting Firm - Herawati, Ega Safira; Meini, Zumratul; Digdowiseiso , Kumba (CV ODIS, 2023)
This study uses a type of descriptive research quantitative approach which is measured using a multiple liner-based renier-based method by making data tabulation data based on the results of answers from respondents with SPSS V26.00. The population of this study is one of the Public Accounting Firms in South Jakarta. With a sample of 12 Public Accounting Firms (KAP) with a total of 100 respondents. Hypothesis testing uses partial tests (t-tests) and simultaneous tests (f-tests). The test results prove that the results of data analysis using partial tests (t-tests), namely Competence has a positive and significant effect on audit quality, Professional Ethics has a positive and significant effect on audit quality, and Information Technology has a positive and significant on audit quality. The results of data analysis using simultaneous tests (f tests) namely Competence, Professional Ethics, and Information Technology have a positive and significant effect on audit quality